The need for transformative changes in the use of Indigenous knowledge along with science for environmental decision‐making in the Arctic - Helen C. Wheeler; Finn Danielsen; Maryann Fidel; Vera Hausner; Tim Horstkotte; Noor Johnson; Olivia Lee; Nibedita Mukherjee; Amy Amos; Heather Ashthorn; Øystein Ballari; Carolina Behe; et al. (People and Nature, 2020)
Abstract Recent attention to the role of Indigenous knowledge (IK) in environmental monitoring, research and decision‐making is likely to attract new people to this field of work. Advancing the bringing together of IK and science in a way that is desirable to IK holders can lead to successful and inclusive research and decision‐making. We used the Delphi technique with 18 expert participants who were IK holders or working closely with IK from across the Arctic to examine the drivers of progress and limitations to the use of IK along with science to inform decision‐making related to wildlife, reindeer herding and the environment. We also used this technique to identify participants' experiences of scientists' misconceptions concerning IK. Participants had a strong focus on transformative change relating to the structure of institutions, politics, rights, involvement, power and agency over technical issues advancing or limiting progress (e.g. new technologies and language barriers). Participants identified two modes of desirable research: coproducing knowledge with scientists and autonomous Indigenous‐led research. They highlighted the need for more collaborative and coproduction projects to allow further refinement of approaches and more funding to support autonomous, Indigenous‐led research. Most misconceptions held by scientists concerning IK that were identified by participants related to the spatial, temporal and conceptual scope of IK, and the perceived need to validate IK using Western science. Our research highlights some of the issues that need to be addressed by all participants in research and decision‐making involving IK and science. While exact approaches will need to be tailored to specific social‐ecological contexts, consideration of these broader concerns revealed by our analysis are likely to be central to effective partnerships. A free Plain Language Summary can be found within the Supporting Information of this article.